Trigeminal Neuralgia Management with Varmam Therapy and Siddha Medicine – A Case Report - C. Kalaiarasi,; R. Keerthika,; D. Periyasami,; N. J. Muthukumar, (Journal of Natural Remedies, 2024)
A 48 year old female staff nurse from Chennai consulted in the Varma Maruthuvam Outpatient Department of APH-NIS, Chennai presented with complaints of sudden and severe stabbing pain with burning sensation at the left half of the maxillary and mandibular region for one year. After her MRI scan was done, she was diagnosed with trigeminal neuralgia due to vascular compression. The patient had consulted an allopathic hospital and used carbamazepine for the long term. She experienced some temporary relief, but the episodes occurred for a short while, and she felt drowsy. For further improvement, she came for Varmam treatment. The present study is a case report of typical Trigeminal Neuralgia (TN) that was treated with Siddha Varmam therapy along with Amukkarachooranam, Arumugachenduram and Arakku thailam for two months. This case report showed a promising reduction in pain episodes and recurrence following treatment, as measured by the Visual Analogue Scale (VAS) score. This study sheds light on the fact that Varmam therapy with concomitant medicines has a promising effect in the management of trigeminal neuralgia.